2013
DOI: 10.1161/circheartfailure.112.000062
|View full text |Cite
|
Sign up to set email alerts
|

Dilated Cardiomyopathy

Abstract: A 42-year-old woman presented herself to the emergency services in cardiogenic shock. She had a history of progressively worsening breathlessness for the past year; however, no medical evaluation had been performed earlier. At presentation, her pulse rate was 110 beats per minute, regular, and low volume, and her blood pressure was 90/70 mm Hg. On auscultation, third heart sound was present, but no murmurs were heard. Soon after presentation, she had an asystolic cardiac arrest. However, she was resuscitated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
1
4
1
Order By: Relevance
“…To our knowledge, no case of hypophysitis-induced secondary adrenal insufficiency along with heart failure successfully treated with cortisol replacement therapy alone has been reported in the literature. The findings of this case are consistent with those of previous cases [1][2][3] in terms of long-term fatigue that was considered normal after delivery. Therefore, adrenal insufficiency may remain undiagnosed after delivery, suggesting the possible existence of women with undiagnosed endocrine insufficiency, who may have heart failure in the future.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To our knowledge, no case of hypophysitis-induced secondary adrenal insufficiency along with heart failure successfully treated with cortisol replacement therapy alone has been reported in the literature. The findings of this case are consistent with those of previous cases [1][2][3] in terms of long-term fatigue that was considered normal after delivery. Therefore, adrenal insufficiency may remain undiagnosed after delivery, suggesting the possible existence of women with undiagnosed endocrine insufficiency, who may have heart failure in the future.…”
Section: Discussionsupporting
confidence: 91%
“…Few cases of reversible cardiomyopathy accompanied by Sheehan syndrome have been reported. [1][2][3] These cases have the common characteristics of a late diagnosis of Sheehan syndrome after delivery (>2 years) and recovery of cardiac function after hormone replacement therapy, including glucocorticoid therapy. One of the previous cases was initially diagnosed with peripartum cardiomyopathy and showed no improvement of cardiac function with standard medications for heart failure until hormone replacement therapy was initiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rare, there have been reports of late onset hypopituitarism presenting with new cardiomyopathy. Doshi et al reported a 42-year-old female with new onset cardiomyopathy secondary to hypopituitarism that occurred 14 years after a postpartum hemorrhage (20). In contrast to the present case, their patient's cardiomyopathy completely reversed with replacement hormones.…”
Section: Discussioncontrasting
confidence: 72%
“…Pituitary gland has a large secretory reserve, and >75% must be destroyed before clinical manifestations of hypopituitarism are evident. [ 2 ] SS, therefore, often evolves slowly and is diagnosed late. Increased pituitary volume during pregnancy, small sella size, coagulopathy, and autoimmunity are the proposed factors in the pathogenesis of SS.…”
Section: Discussionmentioning
confidence: 99%